FAKTOR PENYEBAB DAN PERTIMBANGAN HAKIM DALAM PUTUSAN NOMOR 14/PDT.G/2014/PN.RNO ANTARA MASYARAKAT DAN PEMERINTAH KABUPATEN ROTE NDAO - Manafe, Jefry O; Aloysius, Sukardan; Mauritsius, Darius (Petitum Law Journal, 2023)
Land disputes are unavoidable in this day and age, this is because land disputes arise from complaints from a party (person / agency) containing objections and demands for land rights, priorities and ownership in the hope of obtaining administrative settlements in accordance with applicable regulations. The problems in this thesis are: (1) What are the factors that cause land disputes between landowners in Sanggoen Village and the Government of Rote Ndao Regency in Civil Case Decision Number 14/Pdt.G/2014/PN.Rno? and (2) What is the position of land grants against the issuance of certificates of ownership on behalf of Executive and Legislative Officials in Civil Case Decision Number 14/Pdt.G/2014/PN.Rno?. This research is a normative legal research by collecting, reading, tracing a number of library materials and analyzing Decision Number 14/Pdt.G/2014/PN.Rno. Data processing is carried out by several processes, namely the data obtained is studied then processed and analyzed. The last stage is drawing conclusions from the data that has been processed. The results of this study show: (1) factors causing land disputes between landowners in Sanggoen Village and the Government of Rote Ndao Regency, namely: The annexation of the Plaintiffs' land by issuing certificates to 40 Executive and Legislative Officials in Rote Ndao Regency and the Plaintiffs' and Defendants' proof that the disputed land is their legitimate property and (2) The position of the land grant against the issuance of certificates of ownership on behalf of 40 Executive and Legislative Officials, namely: referring to Article 1365 of the Civil Code, the issuance of certificates which is a product of the National Land Agency of Rote Ndao Regency contains legal defects. The certificate does not have binding legal force and should be canceled by law.